ЧИСЛЕННО-ПОЛЕВОЙ АНАЛИЗ СИЛОВЫХ И ЭНЕРГЕТИЧЕСКИХ ПРОЦЕССОВ В ТУРБОГЕНЕРАТОРЕ ПРИ НЕСИММЕТРИИ НАГРУЗКИ - Милых, В.И.; Потоцкий, Д.В. (Інститут електродинаміки НАН України, Київ, 2017)
Assessing the impact of load asymmetry of turbo-generator (TG) on the power and energy processes in it based on the numerical-field analysis within the constraints regulated by the standards. Methodology. Mathematical model of TG has been constructed on the method of symmetrical components of the three-phase current system. The unbalanced system of the currents is used for calculations of rotating magnetic fields. Thus the temporal functions of the electromagnetic and power quantities which are subjected to the harmonic analysis are obtained. Results. Calculations are conducted on a three-phase 35 MW TG during its work under autonomous unbalanced loading. The analysis of the temporal functions of the electromagnetic torque and the forces acting on the winding cores and the stator core ferromagnetic part has been executed. The distribution of power of their coefficients according to the phase windings was revealed. Originality. Problems of the TG exploitation at unbalanced loading are detected by the consideration of its electromagnetic system on the whole, but not its simplified local parts, as usual. The basis of the analysis is a new method constructed on the discrete temporal functions of the various quantities revealed by a multiposition numerical calculations of rotating magnetic fields. Practical value. Analysis of the TG work at unbalanced loading showed the problems of a power and electromagnetic character. It is shown that the temporal functions of the forces acting on the stator core rods and its tine generally similar to what it was at the symmetrical load, but the compressive forces acting on the core in general increased. Electromagnetic moment has a very strong pulsation which amplitude reaches 23% of its average value. The powers and their phase windings coefficients are distributed very unevenly. The TG design problems, the solutions of which must take into account the information received, are indicated. This makes it possible to provide for measures to ensure a durable and reliable operation of the TG. References 10, tables 3, figures 6.